Pengaruh Harga, Promosi, dan Suasana Toko (Store Atmosphere) Terhadap Loyalitas Pelanggan Ask Coffee Marelan - Tara Febrianti; Aisyah Azhar Adam (Forum Kerjasama Pendidikan Tinggi, 2026)
This study aims to examine the effect of price, promotion, and store atmosphere on customer loyalty at Ask Coffee Marelan. This research is a quantitative study with an associative approach. Data were collected through questionnaires distributed to 100 respondents who are customers of Ask Coffee Marelan. The analytical methods used include multiple linear regression, t-test, F-test, and the coefficient of determination (R²) with the help of SPSS 27. The results of the t-test show that Price (X1) has a t-value of 6.724, which is greater than the t-table value of 1.984, with a significance level of 0.000 < 0.05, indicating a positive effect. Thus, H1 is accepted and H0 is rejected, meaning that Price (X1) has a positive and significant effect on Customer Loyalty (Y). Promotion (X2) has a t-value of 2.944, which is greater than the t-table value of 1.984, with a significance level of 0.004 < 0.05, indicating a positive effect. Thus, H2 is accepted and H0 is rejected, meaning that Promotion (X2) has a positive and significant effect on Customer Loyalty (Y). Store Atmosphere (X3) has a t-value of 2.056, which is greater than the t-table value of 1.984, with a significance level of 0.043 < 0.05, indicating a positive effect. Thus, H3 is accepted and H0 is rejected, meaning that Store Atmosphere (X3) has a positive and significant effect on Customer Loyalty (Y). Furthermore, the F-test results indicate that the three variables simultaneously have a significant effect on Customer Loyalty (Y) at Ask Coffee Marelan.